PERSEPSI MASYARAKAT TERHADAP KELESTARIAN HUTAN MANGROVE DESA TANJUNG BAIK BUDI KECAMATAN MATAN HILIR UTARA KABUPATEN KETAPANG - Norhidayati, .; Muin, Sudirman; Yani, Ahmad (JURNAL HUTAN LESTARI, 2018)
Utilization of mangrove forest products both in the form of wood and non-timber products, and land clearing for agricultural land and ponds by the community around the mangrove forest without any effort to preserve the mangrove ecosystem makes the existence of mangrove forests in the village Tanjung Baik Budi many are damaged so that it reduces the area of mangrove forests and disrupts the ecosystem. This study aims to examine the public perception of the sustainability of mangrove forests, and analyze the relationship between the level of community dependence, level of knowledge, level of income and community perceptions of the sustainability of mangrove forests in the village Tanjung Baik Budi sub-district Matan Hilir Utara districts Ketapang. Data collection using methods Random Sampling with interview techniques and questionnaire tools. Correlation analysis Kendall Tau. The results of this study indicate that the public perception of the sustainability of mangrove forests has a positive perception. There is a positive and significant relationship between the level of knowledge, the level of dependence on mangrove forests and community perceptions. There is a positive relationshi not the level of income significance with public perception.Keywords: Community, Mangrove Forest, Perception, Sustainability Of Mangrove Forests